IMPLEMENTASI PEMAKAIAN ALAT BANTU PENGAMBILAN KEPUTUSAN (ABPK) PADA AKSEPTOR KB DI WILAYAH KERJA UPT PUSKESMAS PANARUNG KOTA PALANGKARAYA - Muliana; Istiqamah, Istiqamah (LPPM Universitas Sari Mulia, 2024)
Background:The use of Decision Support Tools (DST) focuses on counseling because clients need to choose a method that makes them feel comfortable and satisfied. They also need to understand the side effects, how to use their chosen method, when to return for follow-up, how to receive help and support in using family planning, how to handle issues with the method used, and that they can switch methods if they wish. Objective:To determine the implementation of the use of Decision Support Tools (DST) among family planning acceptors. Method:This research is a descriptive quantitative study. The sampling technique used is total sampling. The population and sample consisted of 30 midwives providing family planning services in the working area of UPT Puskesmas Panarung, Palangkaraya. Results:The study found that the majority of respondents did not adequately implement DST, with 19 midwives (63%) showing low implementation, and a mean score of 8.23. The highest lack of implementation was found in the section on tips for conducting family planning counseling, with 28 respondents (93%) not applying it well. This was followed by the “decision-making wheel” and DST tab section, with 25 respondents (83%) showing poor implementation, and lastly, the contraceptive methods section, with 20 respondents (67%) not applying DST adequately. Conclusion:It can be concluded that out of the 30 respondents in this study, most midwives (19 or 63%) inadequately implemented DST in family planning counseling, while only 11 midwives (37%) applied it properly. The use of DST during counseling can help clients make the right contraceptive choices, assist in problem-solving, and serve as a support tool for health workers. DST is one of the key components to achieving successful counseling outcomes. Keywords: DST, Implementation